Hurricane Risk, Happiness and Life Satisfaction. Some Empirical Evidence on the Indirect Effects of Natural Disasters - Michael Berlemann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
As a consequence of climate change, certain types of natural disasters become either more likely or more severe. While disasters might have numerous direct (typically negative) e ects, the e ect of an increase of natural disaster risk on individual well-being is often neglected. In this paper we study the e ects of natural disaster risk on self-reported happiness and life satisfaction at the example of tropical storms. Combining several waves of the World Values Survey and appropriate storm data we find that disaster risk tends to have little systematic e ect on self-reported happiness, once we correct for individual characteristics. However, hurricane risk turns out to decrease life satisfaction significantly. We conclude that when individuals evaluate their long-term satisfaction with their life, disaster risk is perceived as threat to individual well-being.
Keywords: I31; Q54; Q51; 330